Fibroblast Growth Factor-2 Enhances Expansion of Human Bone Marrow-Derived Mesenchymal Stromal Cells without Diminishing Their Immunosuppressive Potential - Jeffery J. Auletta; Elizabeth A. Zale; Jean F. Welter; Luis A. Solchaga (Stem Cells International)
Allogeneic hematopoietic stem cell transplantation is the main curative therapy for many hematologic malignancies. Its potential relies on graft-versus-tumor effects which associate with graft-versus-host disease. Mesenchymal stromal cells (MSCs) possess immunomodulatory properties that make them attractive therapeutic alternatives. We evaluated the in vitro immunosuppressive activity of medium conditioned by human MSCs from 5 donors expanded 13 passages with or without FGF-2. FGF-2 supplementation increased expansion 3,500- and 240,000-fold by passages 7 and 13, respectively. There were no differences in immunosuppressive activity between media conditioned by passage-matched cells expanded under different conditions, but media conditioned by FGF-treated MSCs were superior to population doubling-matched controls. The immunosuppressive activity was maintained in three of the preparations but decreased with expansion in two. The proliferation induced by FGF-2 did not result in loss of immunosuppressive activity. However, because the immunosuppressive activity was not consistently preserved, caution must be exercised to ensure that the activity of the cells is sufficient after extensive expansion.